Stereoselective methodology for 1-aryl-1-alkyl epoxides via chromium tricarbonyl complexes - Davies, S; Loveridge, T; Clough, J (1997)
Treatment of (1RS, SSR)-(1-phenylsulfinyl-2-valeryl benzene) chromium tricarbonyl 2 with a sulfur ylide results in a highly diastereoselective epoxide formation (d.s.>96:4). Regioselective opening of the epoxide, employing an in situ trapping protocol, allows the synthesis of a highly functionalised, diastereomerically pure benzylic alcohol.